Canadian policies for families with very young children in international perspective - Shelley Phipps (Luxembourg Income Study (LIS), 2009)
This chapter compares Canadian policies for families with children under the age of three with policies available in eight other affluent countries (Finland, France, Germany, Italy, Norway, Sweden, the UK, and the US), three from each of Esping-Andersen's 'three worlds' of welfare capitalism. Within Canada, the province of Quebec has recently introduced its own system of maternity and parental benefits; these are also discussed. For families with very young children, cash maternity and/or parental benefits are particularly important and are thus the focus of the analysis. The first section of the chapter provides an overview of what is available in each of the countries studied; the second section calculates maternity/parental benefit entitlements for five 'sample' new parents; the third uses LIS microdata to compare over-all financial well-being of families with very young children. The chapter concludes that the duration of Canadian maternity and parental benefits compares quite favorably with what is available elsewhere, but the level of benefits offered is rather low. Ceilings on maternity/parental benefits in some countries, including Canada, mean that the effective replacement rate is lower than the nominal replacement rate. Since male earnings are typically higher than female earnings, this may discourage fathers from taking up benefits. Some countries have implemented inducements for men to take parental leaves (e.g., by allocating part of the leave for men only in Sweden, Norway or Quebec). Scandinavian countries are particularly flexible about allowing parents to extend benefit periods by returning to work part-time while collecting partial benefits; Canada might consider moving in this direction to allow families greater freedom in how to use their entitlements. Finally, analysis conducted using the LIS data show that while social transfers play a vital role in reducing the depth of poverty, the Canadian social transfer package leaves more families with very young children in poverty than is the case in the other countries studied except Italy and the U.S.
Keywords: 330; Familienpolitik; Kinderbetreuung; Elternzeit; Sozialstaat; Vergleich; Kanada